Cover trees for fruit trees? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Richard Funyep, of the CAPA-DL group, BP 54, Makénéné, Province du Centre, Cameroon, asks readers for advice on selecting a cover tree. 'We work in a humid forest zone with an equatorial climate characterised by two dry seasons: a short one from...